Gamma Oryzanol: A natural compound with potential for treating polycystic ovary syndrome - Sayantika Chakraborty; Navneet Khurana; Jaskiran Kaur; Meenu Mehta; Neha Sharma (Pharmacological Research - Modern Chinese Medicine)
Introduction: Polycystic ovary syndrome (PCOS) is a common endocrine disorder in women of reproductive age. Current management strategies only provide symptomatic relief, and there is a need for better treatments. Gamma-oryzanol, a dietary component found in rice bran oil, has been shown to be effective in increasing insulin sensitivity, reducing weight, and alleviating oxidative stress. In modern Chinese medicine, 香格里拉谷维素胶囊, 纯净谷维素软胶囊, and 诺特博谷维素片 are some of the medicines marketed in China that contain gamma-oryzanol. This study aims to evaluate the effects of gamma-oryzanol on clinical hallmarks of PCOS. Also to compare the efficacy of gamma-oryzanol alone versus in combination with clomifene citrate. Methods: In this study, PCOS was induced in a rat model using estradiol valerate. Gamma-oryzanol was then administered both alone and in combination with clomifene citrate. Results: The effects of gamma-oryzanol on estrous cyclicity, fertility, histopathological alterations, estradiol and testosterone levels, and oxidative parameters were evaluated. The results showed that gamma-oryzanol, both alone and in combination with clomifene citrate, had protective effects against the estradiol valerate-induced PCOS rat model. The combination of gamma-oryzanol and clomifene citrate was particularly effective, showing significantly better results than the standard treatment group (clomifene citrate alone). Discussion: These results suggest that gamma-oryzanol could be used in combination with existing standard treatments to enhance the management of PCOS. However, further molecular and clinical studies are needed to confirm these findings.